How should we treat pet robots? - Li, Wei; Zhang, Zhonghua; Li, Shuang; Wu, Wei (Acta Bioethica, 2025)
Pet robots can overcome the shortcomings of pets and accompany people instead of pets. There are also some ethical concerns about pet robots, including that pet robots will cause people to deceive themselves, that people's attachment to pet robots will make people miserable, that people will change their original value hierarchy, and that people will behave unethically toward pet robots. To make pet robots better integrate into society, people must treat them correctly, such as enjoying the happiness brought by pet robots, strengthening the independent training of robot pets, not easily changing the value hierarchy of self and being forbidden to behave immorally towards pet robots.